Biomedical Science Day 2024 - Sara Alnasir Kassam (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Biomedicine Student Ambassador, Sara A Kassam, recounts the events that she helped organise and execute as part of Biomedical Science Day 2024. Working closely with Tahmina Hussain, Matthew Jones and several other ambassadors, events were run in tandem across two sixth form colleges and at NHSBT Manchester. Ambassadors and organisers share their thoughts on how the events went and what they gained from the experience.